Exploring the Underlying Ways of Enhancing Critical Thinking Skills - Sharma, Lok Raj; Bhattarai, Rajendra; Humagain, Abhimanyu; Subedi, Shyam Prasad; Thapa, Samrakshika; Acharya, Hareram (International Research Journal of MMC, 2023)
Critical thinking skills in the present dynamic and rapidly changing world are crucial skills that enable individuals to engage in rational and independent thinking to make decent and consistent decisions. This article aims at exploring multifarious underlying ways of enhancing critical thinking skills. It provides readers with definitions of critical thinking and critical thinking skills. It pinpoints key components of critical thinking, barriers to critical thinking, and the major strategies for enhancing these skills. Qualitative data related to critical thinking skills were gathered in the forms of lexes and lexical expressions through a scrupulous review of journal articles, website documents and relevant books published between 1984 and 2023. They served as secondary sources of qualitative data that were explored and analyzed through instances that led to broader concepts regarding critical thinking skills. It is concluded that both acquisition and application of these skills were imperative for individuals to adeptly formulate their fair decisions. Teachers, students, researchers and critics will find this article highly valuable as it equips them with the necessary skills to think critically and make well-versed decisions about a given subject matter.